The Personality and Psychological Stress Predict Major Adverse Cardiovascular Events in Patients With Coronary Heart Disease After Percutaneous Coronary Intervention for Five Years. Issue 15 (April 2016) - Du, Jinling; Zhang, Danyang; Yin, Yue; Zhang, Xiaofei; Li, Jifu; Liu, Dexiang; Pan, Fang; Chen, Wenqiang
Abstract : Abstract: To investigate the effects of personality type and psychological stress on the occurrence of major adverse cardiovascular events (MACEs) at 5 years in patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI). Two hundred twenty patients with stable angina (SA) or non-ST segment elevation acute coronary syndrome (NSTE-ACS) treated with PCI completed type A behavioral questionnaire, type D personality questionnaire, Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale (SAS), Trait Coping Style Questionnaire (TCSQ), and Symptom Checklist 90 (SCL-90) at 3 days after PCI operation. Meanwhile, biomedical markers (cTnI, CK-MB, LDH, LDH1 ) were assayed. MACEs were monitored over a 5-year follow-up. NSTE-ACS group had higher ratio of type A behavior, type A/D behavior, and higher single factor scores of type A personality and type D personality than control group and SAP group. NSTE-ACS patients had more anxiety, depression, lower level of mental health ( P  < 0.05; P  < 0.01), more negative coping styles and less positive coping styles. The plasma levels of biomedical predictors had positive relation with anxiety, depression, and lower level of mental health. Type D patients were at a cumulative increased risk of adverse outcome compared with non-type D patients ( P  < 0.05). Patients treated with PCI were more likely to have type A and type D personality and this tendency was associated with myocardial injury. They also had obvious anxiety, depression emotion, and lower level of mental health, which were related to personality and coping style. Type D personality was an independent predictor of adverse events.